Pathogen Security-Help or Hindrance? - Morse, Stephen A. (Frontiers in Bioengineering and Biotechnology, 2015)
Events over the past 15 years have resulted in the promulgation of regulations in the United States to enhance biosecurity by restricting the access of pathogens and toxins (i.e., biological select agents and toxins [BSAT]), which pose a severe threat to human, animal or plant health or to animal or plant products, to qualified institutions, laboratories, and scientists. These regulations also reduce biosafety concerns by imposing specific requirements on laboratories working with BSATs. Furthermore, they provide a legal framework for prosecuting someone who possesses a BSAT illegally. With the implementation of these regulations has come a discussion in the scientific community about the potential of these regulations to affect the cost of doing BSAT research and international collaborations, or whether it would stop someone with a microbiological background from isolating many of the select agents from nature.